Cross-activity of honeybee queen mandibular pheromone in bumblebees provides evidence for sensory exploitation. (7th November 2019) - Princen, Sarah A; Van Oystaeyen, Annette; Petit, Clément; van Zweden, Jelle S; Wenseleers, Tom
Abstract: The evolutionary origin of queen pheromones (QPs), which regulate reproductive division of labor in insect societies, has been explained by two evolutionary scenarios: the sender-precursor hypothesis and the sensory exploitation hypothesis . These scenarios differ in terms of whether the signaling system was built on preadaptations on the part of either the sender queens or the receiver workers. While some social insect QPs—such as cuticular hydrocarbons—were likely derived from ancestral fertility cues and evolved according to the former theory, the honeybee's queen mandibular pheromone (QMP) has been suggested to act directly on preexisting gene-regulatory networks linked with reproduction. This is evidenced by the fact that QMP has been shown to also inhibit ovary activation in fruit flies, thereby implying exploitation of conserved physiological pathways. To verify whether QMP has similar effects on more closely related eusocial species, we here tested for QMP cross-activity in the bumblebee Bombus terrestris . Interestingly, we found that the non-native QMP blend significantly inhibited egg laying in both worker and queen bumblebees and caused accompanying shifts in ovary activation. The native bumblebee QP pentacosane, by contrast, only inhibited the reproduction of the workers. Overall, these findings support the hypothesis that honeybee QMP likely evolved via a route of sensory exploitation. We argue that such exploitation could allow social insect queens to produce compounds that manipulate the workers to remain sterile, but that a major hurdle would be that the queens themselves would have to be immune to such compounds. Abstract : Bumblebees are forced to bend the knee to honeybee queen pheromones. We show that the honeybee-specific queen mandibular pheromone (QMP) that stops honeybee workers from reproducing, also inhibits reproduction in bumblebee workers and queens, thus exploiting physiological pathways that are highly conserved in insects. In this way, it is possible for social insect queens to evolve manipulative pheromones, that is, if they can overcome the hurdle to be immune to the pheromones themselves.